Theoretical bases of forming for future physical rehabilitation specialists on readiness to health saving activity. - Bielicova N.O (Kharkov National Pedagogical University, 2010)
The structure of preparation of future specialist is considered on a physical rehabilitation. An analysis is carried out over 30 literary sources. It is set that readiness of future specialist includes such structural components: motivational, cognitive, operation and personality. It is marked that a specialist owns knowledge about a health, healthy life style, health saving technologies. Also he realizes the value of health and ready to realize the knowledge in professional activity. Emphasized necessity of improvement of indexes of personality qualities and professional culture.